STUDY ON GROWTH AND BIOMASS OF OCIMUM SANCTUM PLANTS AND PROTEIN PROFILING OF TRICHODERMA HARZIANUM - PADMAVATHI TALLAPRAGADA (International Journal of Pharma and Bio Sciences, 2013)
The capability of the bio-control agent Trichoderma harzianum to trigger plant growth and improvement in biomass response was investigated by inoculating roots of medicinal plant (Ocimum sanctum) seedlings with Trichoderma harzianum in pots, under aseptic, green house environmental conditions. Trichoderma harzianum was isolated from ten different agro climatic zones of Karnataka. Biological and biochemical analysis revealed that inoculation with T. harzianum initiated increased Phosphate (P), Nitrogen (N) and soluble sugars uptake by the O. sanctum plants. Inoculation with T. harzianum increased the biomass of the plants in terms of height, number of leaves and number of branches, providing evidence that T. harzianum induce growth and increased biomass mechanisms in plants. The whole cell protein was extracted from all the ten isolates of T. harzianum and then subjected to electrophoresis (SDS-PAGE). The protein profile on the gel was scored and the dendrogram was constructed using Phylip software of T. harzianum. Exploiting bio-control agents to enhance the plant growth and biomass production of medicinal plants is a topic of current interest.